Carotenoids Extracted from Promising Clones of Criolla Potato (Solanum tuberosum Group Phureja) for Food Industry - Leyton Forero, G.; Abdo, R.; Prieto, L.; Poveda Pisco, J.C.; Ceron Lasso, M.S. (Dialnet, 2025)
The carotenoids are natural pigments that contribute to the replacement of the synthetic colorants which are still used in food industry. With this aim, the carotenoids from 15 promising clones and one commercial variety, named Yema de Huevo, of Criolla potato (Solanum tuberosum Group Phureja) supplied by Corpoica were extracted and evaluated. The tubers lyophilized for 72 h by triplicate, and their carotenoids extracted with acetone and hexane. Absorbance of the supernatants obtained after centrifuging measured using spectrophotometry at intervals of 3 nm. Presence of carotenoids was also confirmed by thin layer chromatography. Absorbance values showed a presence of lutein-5, 6-epoxide in clones 2, 4, 5, 6, 7, 8, 15, and α-carotene in clones 3, 10, 11, 12, 13, 14, 16, 17, and commercial variety. The promising clones 11, 12 and 14 were selected due to their higher carotenoid concentration. Their carotenoids extracted were evaluated their stability under different pH, temperature, and light conditions. A decrease in the color intensity was observed at 13.5 and 1.0 pH. There were not significant changes of color intensity at 50 and 70 °C temperatures. This carotenoids exposure to the light displayed a decrease in the absorbance. After, a commercial colorless yogurt was dyed with the selectedcarotenoids. Carotenoids from promising clone 14 showed higher pigmentation according to the spatial coordinates CIELAB of L*48.66 a*-1.65 b*5.63.Accepted for publication: August 15, 2013.